FENOMENA PERKAWINAN SUKU PEDALAMAN MENYOROTI PRAKTEK BUDAYA DAN GENDER DALAM TRADISI SUKU BADUY - Badruzaman, Dudi (Jurnal Sosial Humaniora, 2020)
The Baduy community with the concept of being left behind, isolated, and uncivilized (uncivilized), as well as life wrapped up by traditional elements, always refers to adat beliefs in their actions and behaviors every day, namely the presence of karuhun teachings, which they always hold fast, Wrong one concrete proof of this is exemplified by the Baduy people who translate the form of affection through marriage rituals. The purpose of this study was to determine the marriage ceremony of the Baduy tribe, which took place, as well as to know the theological assumptions and theological meaning of the Baduy community about the practice of marriage in the Sundanese Wiwitan religious tradition. The collection process is carried out through interview, observation and documentation techniques. The results and conclusions of this study that the Baduy people consider that the marriage ritual is an obligation mandated by the karuhun. First, the ritual is only done once in a lifetime. Second, the Baduy customary rules advocate not polygamy. Third, the marriage procedures practiced by the Baduy community are an important point of the Baduy customary rules. In Baduy community life, the position of women and men is balanced Compliance is the key to harmony and integrity of the Baduy community in living life in the world.